Analisis Perilaku Konsumen dinilai Dari Indeks Sikap Konsumen Pada Restoran Nasi Gajah (Studi Kasus Pada Restoran Nasi Gajah Kota Depok) - Dini Bapiani; azwar azwar; Titik Purwinarti (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
Currently culinary business trends provide opportunities and challenges to the actors and goverment as stakeholders. Business actors can choose arid design a suitable strategy to influence consumers by understanding consumer behavior. The research object is Nasi Gajah. Problems of the research object are some aspects has not contributed properly. One of the problems is marketing aspect. Nasi Gajah does not know clearly the market segmentation and how big is a consumer. The purposes this research is analyze and to know consumer behavior, characteristic and consumer opinion about Nasi Gajah with consumer behavior index. This research use survey method with 50th sample that a consumer of Nasi Gajah. To distribute the questionnaire use incidental sampling method and purposive sampling. Data collection method were used observation and studi of literature. Data analyze method this research is descriptive and consumer behavior index. The result of this research are: (1) The Nasi Gajah consumer like it well enough (2) The score of consumer behavior index are 3,15 that consumer liked it well enough Nasi Gajah (3) The consumer characteristic is woman, 21-22 years old, student and live in Depok.